Preface: Shallow lakes from the Central Plains of Argentina - Izaguirre, Irina (2015)
This special issue of Hydrobiologia is devoted to the shallow lakes of the Central Plains of Argentina. The contributors were invited to submit papers dealing with different ecological topics including physical features, climatic and geological characteristics of the region, as well as studies focusing on aquatic communities (fish, zooplankton, phytoplankton and microbial components).